(untitled) (Global Journal of Science Frontier Research, 2019)
A study on standard procedure and time setting for servicing of single jersey and double jersey knitting machine is done in this work. Servicing, maintenance, use of lubrications procedure also studied in this project wok. Servicing is a very vital point for keep machine performance well and for better fabric quality. Here we worked on single jersey and double jersey knitting machines servicing procedure, and time setting.